Paulette Greene papers - Greene, Paulette
Research and collecting file including correspondence, postcards, programs, sale catalogs, book advertisements, newspaper clippings, photographs, and other papers concerning Edna St. Vincent Millay. Relates chiefly to Millay's legacy as a lyric poet, playwright and stage performer, Bohemian artist, and modernist author.
Rare book and manuscript collector and dealer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Millay, Edna St. Vincent, -- 1892-1950.; American drama -- 20th century; American poetry -- 20th century; Bohemianism; Dramatists, American; Lyric poetry; Modernism (Literature); Poets, American -- 20th century; Theater -- United States; Collectors